Catalase Nanocrystals Loaded with Methylene Blue as Oxygen Self‐Supplied, Imaging‐Guided Platform for Photodynamic Therapy of Hypoxic Tumors (Small 41/2021). Issue 41 (14th October 2021) - Zhou, Renbin; Ohulchanskyy, Tymish Y.; Xu, Hao; Ziniuk, Roman; Qu, Junle
Abstract : Catalase Nanocrystals In article number 2103569, Tymish Y. Ohulchanskyy, and co‐authors introduce catalase protein nanocrystals as drug nanocarriers producing molecular oxygen within hypoxic tumors. A prolonged catalytic activity of the nanocrystals enables continuing reaction between catalase and endogenous H2 O2, which generates oxygen, while the nanocrystal porosity allows for soaking with the photosensitizer methylene blue, which converts oxygen to reactive state (singlet oxygen) under light irradiation. Combination of the sustained oxygen supply and increased photoinduced generation of singlet oxygen results in enhanced photodynamic therapy of hypoxic tumors.